(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
In the article the author develops a balanced scorecard staff development section of "Rosenergoatom Concern" OJSC. Balanced scorecard is considered in the article as an instrument of controlling, planning and monitoring of economical security maintenance through human resource management system.